Comparison of Effects of Leukocyte-Rich and Leukocyte-Poor Platelet-Rich Plasma on Pain and Functionality in Patients With Lateral Epicondylitis - Melek YERLİKAYA,; Havva TALAY ÇALIŞ,; Serap TOMRUK SÜTBEYAZ,; Hatice SAYAN,; Nurdan İBİŞ,; Ali KOÇ,; Çiğdem KARAKÜKÇÜ, (Archives of Rheumatology, 2018)
Objectives: This study aims to compare the effect of leukocyte concentration in platelet-rich plasma (PRP) on pain, functionality and post-injection local inflammatory reactions in patients with lateral epicondylitis. Patients and methods: The study included 90 patients (26 males, 64 females; mean age 38.6 years; range 18 to 75 years) with lateral epicondylitis- related pain visual analog scale (VAS) score of ≥5 for more than three months. Patients were randomly assigned into three groups. Normal saline (1.5 mL) was injected in group 1 (control group) while a single dose of leukocyte-poor-PRP (1.5 mL) and leukocyte-rich-PRP (1.5 mL) were injected in groups 2 and 3, respectively. An exercise program was recommended to patients in all three groups. Patients were assessed according to VAS, Patient-Rated Tennis Elbow Evaluation, grip dynamometer and pinchmeter, extensor tendon thickness and cortical derangement at baseline and at fourth and eighth weeks after therapy. All patients were questioned regarding paracetamol use and adverse effects after therapy. Results: No significant differences were detected between groups regarding VAS, Patient-Rated Tennis Elbow Evaluation, grip and pinch measurements, extensor tendon thickness and cortical derangement (p>0.05). In intra-group comparisons, VAS and Patient-Rated Tennis Elbow Evaluation scores obtained at fourth and eighth weeks were significantly decreased in all groups when compared to baseline values (p>0.05). Again, there was no significant difference in the control visit at eighth week when compared to baseline. Assessment of grip and pinch measurements revealed that values obtained at fourth and eighth weeks were significantly increased compared to baseline in all three groups (p<0.05). In leukocyte-rich-PRP group, a significant increase was detected in the values obtained at eighth week compared to those obtained at fourth week, but no significant change was detected in other groups. No significant difference was detected in extensor tendon thickness in any group. No significant difference was detected between groups in terms of paracetamol use and post-injection reactions. Conclusion: According to our study findings, lateral epicondylitis does not seem to affected either leukocyte-rich-PRP or leukocyte-poor-PRP on pain and function in the short term. Leukocyte concentration had no association with post-injection local inflammatory reactions.